Implikasi Kebijakan Pengurangan Sampah Oleh Pemerintah Melalui Kerangka Reduce, Reuse, Recycle: (Studi pada Kelompok Usaha Kembang Setaman Kota Pekanbaru) - Nurmasari Nurmasari; Budi Mulianto; Rijalul Fikri (LPPM Institut Pendidikan Nusantara Global, 2025)
Waste reduction, a target mandated by the Republic of Indonesia's government through legislation, is required of all stakeholders, including the community, involving recycling processes and other advanced methods. This research aims to understand and analyze the achievement of waste reduction by the Joint Business Group (Kelompok Usaha Bersama - KUB) Kembang Setaman. It also seeks to assess the extent of the sustained impact through the application of the reduce, reuse, recycle framework. Utilizing qualitative research methods with in-depth interview techniques, observation, and documentation, data verification and validation are conducted through triangulation and a systematic measurement system using mind manager (open coding, axial coding, selective coding). KUB Kembang Setaman has successfully achieved waste reduction through the reduce, reuse, recycle approach by engaging the community, raising awareness, and making positive contributions to economic and environmental aspects. The implementation of the 3R principles has created significant impacts, both directly and in the long term. Waste reduction measures, reuse of items, and recycling have successfully transformed the paradigm regarding waste in this community. The conclusions drawn from this research are twofold: firstly, in reducing the use and disposal of unnecessary items, and secondly, in creating sustained impacts through changes in behavior and mindset regarding waste.